Manajerial Pembelajaran Moral dan Budi Pekerti dalam Pengembangan Nilai-Nilai Karakter Siswa di Raudhatul Athfal - Ida Nurfarida; Endin Nasrudin; Arfiani Yulianti Fiyul (Institut Madani Nusantara, 2021)
Moral development is related to rules and conventions about what humans should do in their interactions with others. The moral development of a child is much influenced by the environment. Children get character values ??from their school environment, especially from their teachers. Children learn to recognize values ??and behave according to these values, in developing children's morals, the role of teachers is very important, especially when children are young. This research was conducted in all RA in the Sub-Districts of Parungkuda, Sukabumi Regency with a qualitative approach, data collection techniques using observation, interviews, and documentation studies. Based on a thorough data analysis of the implementation of moral learning and character in developing the character values ??of students in RA in the Parungkuda Subdistrict, Sukabumi Regency starts from the planning and implementation has been carried out maximally because it refers to government regulations in implementing learning. It's just that in the implementation of the evaluation it has not done the process correctly. This means that the teacher only does makeshift evaluation activities without using predetermined evaluation principles. While the supporting factors in the implementation of learning are a clear vision and mission, supporting facilities and infrastructure, active learning of students. As for the inhibiting factors in the implementation is the lack of teachers in understanding learning material, lack of parents actively involved in school learning.